Einige Fragen der Flächentheorie - Vosylius, R. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Р. Восилюс. Некоторые вопросы теории поверхностей R. Vosylius. Kai kurie paviršių teorijos klausimai